STRATEGIC CHOICE PERSPECTIVE TO TECHNOLOGICAL CHANGE - Attar, Melis; Temizel, Gamze (European Scientific Journal, ESJ, 2015)
In today‘s work organizations, managing technology – and its role in organizational processes – attracts great attention due to its core significance for the success of the organization life as a whole. In attempting to understand technology-related organizational change, involving complex interactions between management, technology and organization structure, one should not interpret it as solely the adaptation process of organizations to the impact of the technology itself instead organizational actors‘ intervention in shaping the direction of technological change.There has been a long debate between economists and organizational sociologist about the analysis of technological change. When the literature is reviewed, the most crucial result that emerges is the interdependence of technological change on many subjects and thus its complexity. It is not only that change is solely driven by technological and competitive pressures, but also it is influenced by social and political factors. Additionally, organizations are inherently in a constant state of change behind their stable appearance. Technological change is the product of this chronic unpredictability and uncertainty of organizational life; therefore, it is as well a very complex and uncertain process. This volatile and multifaceted nature of the change process is the challenge that demands a greater emphasis on non-technical aspects of it. In this paper, people in organizations are the starting point to discuss inherently complex and uncertain nature of technological change process with reference to case studies in the context of the political nature of the organizations. Instead of assuming that technology-related organizational change is mainly an adaptation to ‗the inherent and unavoidable requirements of technology‘ as in the case in technological determinism, it is suggested that strategic choices within adopting organizations and negotiation processes between dominant coalitions and other organizational actors affect the organizational outcome of technological change. This further indicates the importance of the idea that there is no best way for all organizations rather there are organizationspecific ways for each due to the variance in their cultures, structures and power relations. The stress will be on the argument that technological change, far from being an ‗event‘, is a social and political process and divergent stakeholder interests within organizations shape the outcomes by their strategic choices, decisions and negotiations.